LBH589 reduces oxidized mitochondrial DNA and suppresses NLRP3 inflammasome activation to relieve pulmonary inflammation - Changwen Ning; Fenghua Gao; Zhe Wang; Huaying An; Pengyu Liu; Yanan Sun; Ru Li; Zhuyang Song; Yuanyuan Yuan; Jinlong Li; Jun Ma; Xingwei Jiang; et al. (PLoS ONE, 2025)
The NOD-like receptor protein (NLRP)3 inflammasome plays a critical role in acute respiratory distress syndrome (ARDS) by activating caspase-1, which cleaves the precursor forms of IL-1β and IL-18 into active cytokines and induces pyroptosis by cleaving gasdermin D (GSDMD). LBH589, a pan-histone deacetylase inhibitor, exhibits promising anti-inflammatory and immunomodulatory properties. However, the protective effect and underlying mechanism of LBH589 against ARDS is still unclear. In this study, we aim to determine whether and how LBH589 inhibits NLRP3 inﬂammasome activation while exerting its anti-inﬂammatory effect. Our data demonstrated that LBH589 effectively suppressed NLRP3 inflammasome activation in lipopolysaccharides (LPS)-primed and adenosine triphosphate (ATP)-stimulated J774A.1 cells and bone marrow-derived macrophages (BMDMs), evidenced by attenuated cleaved caspase-1 and IL-1β, IL-18, IL-16 release, as along with reduced GSDMD-mediated pyroptosis and ASC speck formation. Additionally, LBH589 significantly decreased mitochondrial reactive oxygen species (mtROS) and oxidized mitochondrial DNA (Ox-mtDNA), key triggers of inflammasome activation. Importantly, both prophylactic and therapeutic administration of LBH589 inhibited the pro-inflammatory cytokines secretion in lung tissue and ameliorated lipopolysaccharide (LPS)-induced ARDS in mice. These findings suggest that LBH589 may provide therapeutic benefits in ARDS by attenuating NLRP3 inflammasome activation and pyroptosis.